Assessment of socioeconomic vulnerabilities in communities surrounding Kolmani oil field, Bauchi State, Nigeria - Yakubu , Muazu Adamu; Kassem, Semshak Danladi (Kashere Journal of Politics and International Relations, 2025)
The communities around Kolmani River basin have come to limelight since the discovery of huge deposits of hydrocarbon estimated to be over one billion barrels and over 500 billion cubic feet of gas around the basin. The discovery has led to the exposure of communities around Kolmani oil field, thereby making them vulnerable to various socioeconomic threats kidnapping for ransom, cattle rustling, loss of fertile farmlands, and destruction of vital ecosystem. This paper adopts Human security theory which is centered on the wellbeing of persons amidst prevailing threat(s) and social constructivism theory which postulates that identities and interests of purposive actors are constructed by shared ideas, and not given by nature to understand the causal relationship between presence of valuable natural resource and the perceptions/demands of communities therein, as espoused by Alexander Wendt’s tenets of social constructivism. This paper utilized both primary and secondary sources of data, primary data was obtained through KII from community leaders/stakeholders, and secondary data was obtained qualitatively via extant literatures, Newspaper Publications particularly Wikki-Times (A local Newspaper with interests in happenings within Bauchi State). Data obtained was analyzed thematically. Findings reveals that activities of oil exploration has exposed these communities to various forms of insecurity, further finding reveals that the exploration activities have had a significant effects on the fragile ecosystem of the Yankari Games Reserve which is 16km away from the field , amongst other vulnerabilities.